Rancang Bangun Pembangkit Listrik Tenaga Surya (PLTS) 300 WP Dengan Sistem Automatic Transfer Switch (ATS) Untuk Rumah Sederhana - Faisal Fadhlurrahman; Hadi Purnomo (UNIVERSITAS INDRAPRASTA PGRI, 2022)
Indonesia is a tropical country with a large amount of sunlight and high energy potential, with daily radiation ranging from 4.5 to 4.8 kWh/m2. Sunlight is not polusive, it will not run out, but it is free as a renewable energy. As a result, this energy source can be used for electricity using the Solar Power Plant (PLTS) system. The purpose of the study is to study the performance of solar power plants that allow power generation, as well as to understand how efficient they are and how they can be used as a backup power source. vice versa (full automatic).In this auto mode when the PLN power goes out, the automatic electricity will still turn on because the load is taken from the solar power plant. In PLN mode, the load will be fully covered by PLN but if PLN goes out the automatic load will move to the solar power plant and if the PLN load is on it will return to PLN. Solar power plant or off grid mode, this mode is the main priority, namely solar power plants can be used when PLN electricity goes out or want to use full solar power plants as the main load and can be covered for 2 hours and 20 minutes when the battery is in full capacity.